RNAi knockdown of oxytocin receptor in the nucleus accumbens inhibits social attachment and parental care in monogamous female prairie voles - Keebaugh, Alaine C. (Soc Neurosci, 2015)
Oxytocin modulates many aspects of social cognition and behaviors, including maternal nurturing, social recognition and bonding. Natural variation in oxytocin receptor (OXTR) density in the nucleus accumbens (NAcc) is associated with variation in alloparental behavior, and artificially enhancing OXTR expression in the NAcc enhances alloparental behavior and pair bonding in socially monogamous prairie voles. Furthermore, infusion of an OXTR antagonist into the nucleus accumbens (NAcc) inhibits alloparental behavior and partner preference formation. However, antagonists can promiscuously interact with other neuropeptide receptors. To directly examine the role of OXTR signaling in social bonding, we used RNA interference to selectively knockdown, but not eliminate, OXTR in the NAcc of female prairie voles and examined the impact on social behaviors. Using an adeno-associated viral vector expressing a short hairpin RNA (shRNA) targeting Oxtr mRNA, we reduced accumbal OXTR density in female prairie voles from juvenile age through adulthood. Females receiving the shRNA vector displayed a significant reduction in alloparental behavior and disrupted partner preference formation. These are the first direct demonstrations that OXTR plays a critical role in alloparental behavior and adult social attachment, and suggest that natural variation in OXTR expression in this region alone can create variation in social behavior.